Social Factors of Community Disaster Preparedness - Johan Budhiana; Lely Wahyuniar; Mamlukah Mamlukah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Indonesia is prone to disasters because of its geography, geology, water, and population. One way to reduce the risk is for the community to be ready through social factors. The purpose of the study to determine social factors of community disaster preparedness. Methods: the search strategy used Google Scholar, Science Direct, and DOAJ which were searched from 2018-2023. The keywords used were community, disaster preparedness, social capital, community resilience, and social support. The Critical Appraisals Skills Program was then conducted. There were six articles that met the inclusion criteria. Results: The results of all these articles show that social capital, community resilience and social support have a relationship with disaster preparedness through various research methods. The results also show that social factors are strongly related to disaster management, especially disaster preparedness. The facts also show that there is conformity with the theory that social factor determinants can increase community preparedness in the face of disasters. Conclusion: Based on the results of the literature review, social factors including social capital, community resilience and social support significantly influence community preparedness in the face of disasters.